EMPOWERING ADOLESCENTS THROUGH INTERACTIVE TRIVIA PEER-EDUCATION TO PREVENT ACUTE RESPIRATORY INFECTIONS IN BENJOR - Purnomosidi, Muhammad Revi; Mahzalefa, Syarifa Nadia; Zhafirah, Msy. Haura Kaiyyisah; Wulan, Nada Balqis My; Wibisono, Taurisma Aulia Nanda; Andyastanti, Tisnalia Merdya (LPPM Univ. Ibn Khaldun Bogor, 2025)
Acute Respiratory Infection (ARI) is a persistent health problem among rural adolescents in Indonesia, generally influenced by low health literacy and limited access to preventive education. This study aims to determine the effectiveness of an interactive, peer-based educational intervention in improving knowledge and preventive behaviors related to ARI among adolescents in Benjor Village, Malang Regency. A pre-post quasi-experimental research design was used in this study, involving 32 adolescents who were trained to deliver health education through gamified trivia sessions, animated digital media, and participatory discussions. Knowledge assessments were conducted before and after the intervention to measure learning outcomes. The results showed a significant improvement, with an average post-test score increasing by 60% compared to the pre-test score. Participants demonstrated a better understanding of ARI symptoms, transmission routes, and prevention strategies. Furthermore, the peer-based approach was shown to encourage higher engagement, trust, and message retention. These findings suggest that the combination of interactive media and peer education is an effective strategy in improving health literacy and prevention among adolescents. This model offers a scalable and context-sensitive promotive approach to improving health in rural communities with limited resources.